Suppression of flavivirus transmission from animal hosts to mosquitoes with a mosquito-delivered vaccine - Dan Wen; Limin S. Ding; Yanan Zhang; Xiaoye Li; Xing Zhang; Fei Yuan; Tongbiao Zhao; Aihua Zheng (Nature Communications, 2022)
Based on previous research that the Chaoyang virus is an insect-specific flavivirus, only able to replicate in insects and insect cells, authors present this proof-of-concept mosquito-delivered vaccine; they construct a Zika virus focused candidate that can be delivered by mosquito bite, and assess the immune response and protection in mice.